Rodinný dům s provozovnou Světlá - Vondál, Pavel (Vysoké učení technické v Brně. Fakulta stavební, 2017)
Tato bakalářská práce řeší zpracování projektové dokumentace pro provádění stavby rodinného domu s provozovnou. Stavba se nachází na okraji obce Světlá. Obytná část domu je navržena pro trvalé bydlení 4 osob. Provozovna je navržena jako kadeřnictví. K domu je připojena garáž. Nad garáží je plochá střecha s funkcí terasy, nad obytnou částí je sedlová střecha. Dům je dvoupodlažní s částečným podsklepením. Konstrukční systém je zděný, z broušených keramických tvárnic Porotherm. Zdivo je zatepleno polystyrenem. Objekt je navržen v mírně svažitém terénu.

This bachelor’s thesis deals with the processing of project documentation for detached house with establishment. The building is situated on the outskirts of Světlá. The living area of the house is designed for permanent living of 4 people. The establishment is designed as hairdresser's. The house is connected to garage. Above the garage is flat roof with terrace function, above the living part is saddle roof. The house is two-storey with a partial basement. The bricked construction system is made of polished ceramic blocks Porotherm. Ceramic blocks are insulated with expanded polystyrene. The building is designed in slightly sloping terrain.
Family House with Parlor Světlá
Keywords: Rodinný dům; provozovna; sedlová střecha; terasa; částečné podsklepení; keramické tvárnice; kontaktní zateplení; Detached house; establishment; saddle roof; terrace; partial basement; ceramic blocks; contact thermal insulation